2021
DOI: 10.3390/ijerph181910363
|View full text |Cite
|
Sign up to set email alerts
|

Adult Stature Estimation from Radiographic Metatarsal Length in a Contemporary Korean Population

Abstract: The ability to estimate stature can be important in the identification of skeletal remains. This study aims to develop a Korean-specific equation predicting stature using radiographic measurements in the contemporary Korean population. 200 healthy Korean adults, including 102 males and 98 females, were randomly selected (age, range 20–86 years). The first and second metatarsals of the foot were measured by a standing X-ray using a digital medical image viewer. The result showed a statistically significant corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Although the authors demonstrated the correlation between the stature and metatarsal length in the Korean population using radiographically measuring the length of the metatarsal bone in living Koreans, the stature estimation formula using the radiographically measured metatarsal length had a limitation in its practical application because the maximum correlation coefficient (R) was slightly low at 0.48 [ 15 ]. The recent study suggested a novel equation for calculating stature that was derived by taking the real metatarsal bone from a cadaver and measuring it directly, because the metatarsal bone is unaffected by weight-bearing [ 19 , 20 ] The comparison between antemortem stature and the stature measured from cadaver showed no statistically significant difference [ 22 ], despite the fact that it may be debatable to assess the stature from a cadaver whose antemortem stature is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the authors demonstrated the correlation between the stature and metatarsal length in the Korean population using radiographically measuring the length of the metatarsal bone in living Koreans, the stature estimation formula using the radiographically measured metatarsal length had a limitation in its practical application because the maximum correlation coefficient (R) was slightly low at 0.48 [ 15 ]. The recent study suggested a novel equation for calculating stature that was derived by taking the real metatarsal bone from a cadaver and measuring it directly, because the metatarsal bone is unaffected by weight-bearing [ 19 , 20 ] The comparison between antemortem stature and the stature measured from cadaver showed no statistically significant difference [ 22 ], despite the fact that it may be debatable to assess the stature from a cadaver whose antemortem stature is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Regression models based on the corresponding population according to population affinity and region have, however, been proposed for more accurate stature estimation using metatarsals from cadaver, because forensic anthropological population data may demonstrate disparities by population affinity and region [ 13 , 14 ]. Although the authors have previously shown a favorable correlation between the length of the metatarsals as determined by radiography and stature in the Korean population [ 15 ], an additional study was required to develop a formula for determining stature by measuring the actual metatarsal length using a cadaver, however, due to the constraint that metatarsal length through indirect assessment using radiography can differ from the actual length.…”
Section: Introductionmentioning
confidence: 99%